New House Ceremony - Rina Trie Syahputri; Tiarnita Maria Sarjani Br. Siregar; Ribka Manurung; Sandra Hutapea; Yoga Karosekali (Ravine Publisher, 2024)
This research aims to find out about the new house ceremony, specifically in the Batak toba custom, by exploring and documenting what is known as